„Россия поднимается с колен” четверть века спустя: медиалингвистический анализ политической мифологемы - Sładkiewicz, Żanna (Studia Rossica Posnaniensia, 2025)
The focus of this article is the national political myth “Russia is rising from its knees” constituting the foundation of the narrative practices of state propaganda, an effective mechanism of suggestion, inscribed in the national picture of the world, based on archetypal ideas of society and not requiring an evidence base. The significance of the myth in the political sphere lies in the fact that it is based not on intricate intellectual arguments, but on the hypnotization of the masses, updating mythological narratives and appealing to irrational, emotional consciousness. The mythologeme – as a verbal carrier of the myth, a complex type of a sign with the function of a concept and figurative content – serves as a symbolic encoding of the world and consolidation of society. Complex phenomena fitted into a fixed verbal formula are reduced to generally understandable ideas, take hold in collective consciousness via stereotypical nominations and become the subject of faith, not reasoning. The author consistently defines the national myth and the political myth, determines the functions of the political myth, traces the genesis of the mythologeme “Russia is rising from its knees”, its wide distribution in Russian society, its symbolic and semantic content and, finally, the ridicule of this political construct in the corpus of memes. The analyzed Internet memes are a product of collective network creativity, the result of a culture of resistance to political mythology. The article contributes both to the theory and to the practical analysis of the mythology.